Two new synonymies at the generic level in Neotropical Ptomaphagini (Coleoptera, Leiodidae, Cholevinae) - Gnaspini, Pedro; Antunes-Carvalho, Caio; Peck, Stewart B. (Zootaxa, 2016)
We here recognize the genus Excelsiorella (s. str.) Salgado, 2008 as a junior synonym of the genus Adelopsis Portevin, 1907, and Viruana Salgado, 2013, a subgenus of Excelsiorella, as a junior synonym of the genus Parapaulipalpina Gnaspini, 1996. As a consequence, we propose the following new combinations: Adelopsis latissima (Salgado, 2008) n. comb. (from Excelsiorella (s. str.)) and Parapaulipalpina tambopata (Salgado, 2013) n. comb. (from Excelsiorella (Viruana)).